Penanaman Nilai-Nilai Akhlak Terpuji melalui Kegiatan Keislaman Siswa SDI Ibnu Syam Kubang Putih - Hoiriyah Hoiriyah; Nurhasnah Nurhasnah; Ulva Rahmi; Jasmienti Jasmienti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The fact that some students have poor morals-for example, by speaking rudely, leaving class to study, arguing while joking, disrespecting professors, but preferring to come late-is what prompted our investigation. The formulation of the study topic that stems from several problems at SDI Ibnu Sham Kubang Putih is how to instill praiseworthy moral values (morals towards friends and teachers) through student Islamic activities at SDI Ibnu Sham Kubang Putih. The purpose of this research is to find out how the Islamic activities of SDI Ibnu Syam Kubang Putih students can instill good moral values (morals towards teachers and morals towards peers). The descriptive qualitative method was used in the field study conducted. Research with this qualitative descriptive approach is carried out to explain or show events that occur in the field without falsifying or comparing data. This method is expected to provide a more detailed and comprehensive picture of the development of praiseworthy morals among SDI Ibnu Sham Kubang Putih students through their Islamic activities. The Islamic Religion teacher acts as the primary data source of the research, while the students of class III A, the principal, and the homeroom teacher act as supporting informants. To collect data in this study, the researchers used observation - more specifically, they saw how values were instilled directly. Through this Islamic exercise, noble values were demonstrated. In addition, instructors and students were interviewed directly to serve as supporting informants. The research findings show that the Islamic activities conducted at the school are as follows: Quran recitation, Muhadharah, Tahfidz al-Qur'an, and Zuhr prayer in congregation. Islamic activities develop commendable behavioral traits, such as discipline, good manners, clean lifestyle, environmental awareness, responsibility, and mutual respect. During this time, SDI Ibnu Syam Kubang Putih students are forming commendable moral values through Islamic activities by familiarizing them with constructive acts of devotion.